Understanding the Internet of Nano Things: overview, trends, and challenges - Mainor Alberto Cruz Alvarado; Patricia Alejandra Bazán (e-Ciencias de la Información)
Over the years, technological advancements have led to rapid growth of smart environments (offices, homes, cities, etc.). The increase of intelligent environments suggests the interconnectivity of applications and the use of the Internet. For this reason, arise what is known as the Internet of Things (IoT). The expansion of the IoT concept gives access to the Internet of Nano Things (IoNT). A new communication networks paradigm based on nanotechnology and IoT, in other words, a paradigm with the capacity to interconnect nano-scale devices through existing networks. This new paradigm so-called IoNT is presented to the world as an option for various fields of application. Therefore, new challenges and research opportunities have arisen. Consequently, this work aims to investigate state of the art and analyze trends for the use of IoNT, its application and future challenges in different fields of social interest, because IoNT is presented as an option for research with the capacities needed to get involved in many fields of social welfare.  It is concluded that technologies prevail current IoNT literature, applications are focused on health care, and there is no international standardization regarding privacy, security or architecture of nano-networks.